Hedge fund investing : return persistence of style investing and style portfolio performance 1994-2004. - Chua, Janice Hui Li. (2008)
Our applied research reexamines both the return persistence in nine style investing and the active return performance of style portfolios for the sample period from 1994 to 2004. Performance is evaluated in terms of forward-looking information ratios. The active returns and tracking errors are based on returns projected from nine multi-factor projection models.